The changing reality of urothelial bladder cancer: should non‐squamous variant histology be managed as a distinct clinical entity?. (6th March 2015) - Monn, M. Francesca; Kaimakliotis, Hristos Z.; Cary, K. Clint; Bihrle, Richard; Pedrosa, Jose A.; Masterson, Timothy A.; Foster, Richard S.; Gardner, Thomas A.; Cheng, Liang; Koch, Michael O.
<x xml:space="preserve">Abstract</x> Objectives To assess the effect of non‐squamous differentiation (non‐SQD) variant histology on survival in muscle‐invasive bladder urothelial cancer (UC). Patients and Methods A cohort of 411 radical cystectomy (RC) cases performed with curative intent for muscle‐invasive primary UC was identified between 2008 and June 2013. Survival analysis was evaluated using Kaplan–Meier methodology comparing non‐variant (NV) + SQD histology to non‐SQD variant histology (non‐SQD variants). Multivariable cox proportional hazards regression assessed all‐cause and disease‐specific mortality. Results Of the 411 RC cases, 77 (19%) had non‐SQD variant histology. The median overall survival (OS) for non‐SQD variant histology was 28 months, whereas the NV+SQD group had not reached the median OS at 74 months (log‐rank test P < 0.001). After adjusting for sex, age, pathological stage, and any systemic chemotherapy, patients with non‐SQD variant histology at RC had a 1.57‐times increased adjusted risk of all‐cause mortality (P = 0.027) and 1.69‐times increased risk of disease‐specific mortality (P = 0.030) compared with NV+SQD patients. Conclusions While SQD behaves similarly to NV, non‐SQD variant histology portends worse OS and disease‐specific survival regardless of neoadjuvant or adjuvant chemotherapy and pathological stage. Non‐SQD variants of UC could perhaps be considered a distinct clinical entity in UC with goals for developing new treatment algorithms through novel clinical trials.